Pharmacological management of pain in palliative care: Contributions of the Clinical Pharmacist in a convergent care research (Research, Society and Development, 2023)
Faced with the need to alleviate pain suffering in patients facing life-threatening diseases, the objective of this study was to develop a multiprofessional protocol for pain management in palliative care patients. This work is a qualitative research of a convergent care type, developed through the experience of a Pharmacist Resident, the Commission for Palliative Care and Terminality and the Pain Management Team of a teaching hospital in the state of Rio Grande do Sul. Furthermore, meetings were held to review, discuss and standardize the scales for pain assessment according to the care profile, like the selection of eligible drugs according to the World Health Organization's analgesic pain ladder. In addition, new drugs were included to guarantee greater variability in the therapeutic choice and the elaboration of standard prescriptions with the purpose of avoiding prescription errors, guaranteeing greater agility in the prescription process and the adherence to the protocol. After the protocol was elaborated, training was developed for the care teams and the hospital's clinical staff. Therefore, the clinical pharmacist played an extremely important role in the elaboration of the protocol by studying the pharmacotherapy of the eligible drugs in pain management, the rational use of these drugs, adequate management of adverse effects, assistance in the standardization of the scales for the evaluation of pain and participation in the training of care teams.